ANALISIS KEKUATAN BANGUNAN TERHADAP GAYA GEMPA DENGAN METODE PUSHOVER STUDI KASUS GEDUNG ASRAMA PUSDIKLAT PPATK, DEPOK - Tatya Putri Utami; Niken Warastuti (Jurnal Infrastruktur, 2017)
Indonesia is an archipelago country located at a meeting of three tectonic plates so that Indonesia has the potential to experience an earthquake. As a result of the earthquake many buildings are damaged building structures. When an earthquake happens, the building is expected to be able to accept a certain level of earthquake force without significant damage to the structure or if the collapsing structures must be able to give non-linear behavior in the postelasticconditions so that the building's safety level against earthquake and safety of the occupants is more secure. The Pusdiklat PPATK boarding house, Depok is a building which in its development planning is expected to be able to accept the earthquake force and behave non-linearly. But this dormitory building does not yet have data on building resistance to earthquake forces. Therefore it is necessary to analyze this building by using one method of building strength analysis to earthquake forces that is pushover method. This analysis is done using SAP2000 program. The conclusion of the analysis shows that the greater the force (base force) given the greater the displacement that occurs in the building. The maximum earthquake load that the building can accept is 730,383 kN. Based on the ATC-40 performance limit the building is at the level of IO, indicating that the building is safe to use during an earthquake.